Design, synthesis and in-vitro anti-depressant activity evaluation of some 2-styrylbenzimidazole derivatives - Manisha Sahariah; Rubina Chowdhury; Padmanath Pegu; Farak Ali; Rajat Subhra Dutta; Supriya Sahu (SpringerOpen, 2024)
Abstract Background Existing antidepressants possess various adverse effects and so they are not considered as the first line of drug in mild depression. The lack of proper drugs to treat the mild depression on the other hand alleviates severe depressive cases. To overcome this problem, the nucleus of benzimidazole and cinnamic acid having very less toxicity were fused and a small library of 40 compounds was prepared. The library was then screened for ADMET properties and probable toxicity. Those compounds which had not shown any toxicity as well as possessed better in-silico absorption, distribution and metabolism were selected for the first phase of the study. Synthesized compounds were characterized by FTIR, 1H-NMR and 13C-NMR and were screened for in-vitro antidepressant activity by DNPH spectrophotometry. Result The compounds MS-3 and MS-8 had shown good antidepressant activity with IC50 values of 367.19 μM/mL and 184.56 μM/mL against MAO-A and MAO-B, respectively. Conclusion From this study, it can be concluded that the structural requirements for the inhibition of MAO-A and MAO-B were totally different. MAO-A inhibitors required the presence of nitrogen and oxygen containing ring substitutions whereas MAO-B inhibitors required the presence of 4-halogen containing phenyl ring substitutions. Graphical abstract